Pembelajaran Al-Qur’an Hadis Pada Masa Pandemi Covid-19 Dalam Membangun Nilai-Nilai Keimanan Peserta Didik: (Studi Kasus di Madrasah Ibtidaiyah Negeri 1 Cianjur) - Isep Bunbun Sihabudin (Bageur: Jurnal Ekonomi, Sosial, dan Pendidikan, 2025)
Religious education, especially the learning of the Qur'an Hadith, has an important role in shaping the character and faith of students. However, the COVID-19 pandemic, which requires learning to be carried out online and offline, poses a big challenge to the educational process, including in learning the Qur'an Hadith. This study aims to analyze the role of teachers, learning methods, and the impact of learning the Qur'an Hadith on the faith of students at Madrasah Ibtidaiyah Negeri (MIN) 1 Cianjur during the pandemic. This study uses a descriptive qualitative approach with a case study design. Data was collected by conducting in-depth interviews with teachers and students, direct observation of learning activities, and collecting documents related to learning the Qur'an Hadith. The data was analyzed using qualitative analysis techniques, which included data reduction, data presentation, and conclusion drawn. The results of the study show that teachers at MIN 1 Cianjur play a very important role in maintaining the quality of learning the Qur'an Hadith during the pandemic. Learning is carried out through online and offline methods, although there are obstacles to accessing technology. The positive impact of this learning can be seen in increasing faith, discipline in worship, and changing the behavior of students who are more polite and caring for others.